Preparation and characterization of dual layer thin layer lanthanum strontium cobalt ferrite /alumina hollow fiber membrane using dip-coating and brush-coating techniques - Norfazliana Abdullah,; Mukhlis A. Rahman,; Mohd Hafiz Dzarfan Othman,; A.F. Ismail,; Juhana Jaafar, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This paper reports the preparation of the dual layer ceramic hollow fiber membrane that made of alumina and a mixed ion electron conducting (MIEC) material for simultaneous reaction and separation applications. Alumina hollow fiber membrane was prepared using the phase inversion process followed by a sintering technique at elevated temperature. The alumina hollow fiber membrane was used as membrane support onto which a thin and dense layer of lanthanum strontium cobalt ferrite (LSCF) was deposited. The main objective of this study was to investigate the LSCF coating formulations used in the deposition of LSCF layer onto alumina substrate membrane. The sintering temperature of thin LSCF layer was varied to investigate gas-tightness properties of LSCF membrane. A series of characterizations were conducted for both the support and the LSCF membrane. The result showed that the thin layer membranes with thicknesses ranging from 3 to 20 μm were successfully deposited on the surface of alumina hollow fiber support. The sintering process improved the gas-tightness properties but the sintering temperature above 1150oC caused defects on the surface of LSCF membrane.